Antibodies of the immunoglobulin a isotype to novel antigens in early axial spondyloarthritis - Ruytinx, Pieter; Vandormael, Patrick; Quaden, Dana; Luyten, Elien; Geusens, Piet; Vanhoof, Johan; Agten, Anouk; Vandenabeele, Frank; de Vlam, Kurt; Somers, Veerle (Frontiers in Medicine, 2023)
Introduction There is an unmet need for biomarkers to identify patients with axial spondyloarthritis (axSpA). Increasing evidence suggest the presence of autoantibodies in a subset of axSpA patients. The aim of this study was to identify novel IgA antibodies in early axSpA patients and to determine their diagnostic potential in combination with previously determined IgG antibodies against UH (Hasselt University)-axSpA-IgG antigens. Methods An axSpA cDNA phage display library constructed from axSpA hip synovium, was used to screen for novel IgA antibodies in plasma from early axSpA patients. The presence of these antibodies against novel UH-axSpA-IgA antigens was determined in two independent axSpA cohorts, in healthy controls and in patients with chronic low back pain. Results We identified antibodies to 7 novel UH-axSpA-IgA antigens, of which 6 correspond to non-physiological peptides and 1 to the human histone deacetylase 3 (HDAC3) protein. IgA antibodies against 2 of these 7 novel UH-axSpA-IgA antigens and IgG antibodies against 2 of the previously identified antigens were significantly more present in early axSpA patients from the UH cohort (18/70, 25.7%) and the (Bio)SPAR cohort (26/164, 15.9%), compared to controls with chronic low back pain (2/66, 3%). Antibodies to this panel of 4 antigens were present in 21.1% (30/142) of patients with early axSpA from the UH and (Bio)SPAR cohorts. The positive likelihood ratio for confirming early axSpA using antibodies to these 4 UH-axSpA antigens was 7.0. So far, no clinical correlation between the novel identified IgA antibodies and inflammatory bowel disease could be identified. Discussion In conclusion, screening an axSpA cDNA phage display library for IgA reactivity resulted in the identification of 7 novel UH-axSpA-IgA antigens, of which 2 show promising biomarker potential for the diagnosis of a subset of axSpA patients, in combination with previously identified UH-axSpA-IgG antigens.